P.3.07 Prognosis and quality of life in workers with occupational upper limb injury. (April 2019) - Chu, Po-Ching; Hsieh, Ching-Lin; Guo, Yue Leon
Abstract : Objectives: Because literatures about health impact of occupational upper limb injury in injured workers are rare, the study aimed to investigate effects of the injury on workers' prognosis and health-related quality of life. Methods: This was a cross-sectional study of 206 workers with occupational upper limb injury recruited from two teaching hospitals. Their sociodemographic factors, work-related factors, disease severity, return to work status, psychological symptoms, and quality of life were assessed by questionnaire interview at 2 years after injury. Results: The study found that the majority of injured workers were middle-aged (44.0±12.2 years) and men (58.3%). There were 36.3% workers did not return to work at 2 year post-injury. The average EQ-5D was 0.81(ranged from 0 to 1), and the psychological symptoms using 5-item Brief Symptom Rating Scale was 4.19(ranged from 0 to 20). The multivariable linear regression showed that high educated injured workers had poorer quality of life (β=−0.218, p=0.003) and more psychological symptoms (β=6.35, p=0.001) than those with low education. In addition, workers with longer duration (months) of return to work had better quality of life (β=0.0013, p=0.029) and lesser psychological symptoms (β=−0.05, p=0.002), and the workers' compensation scheme may explain the inconsistent with previous studies, and further exploration for other reasons was warranted. Conclusions: The health impact of occupational upper limb injury are multiple aspects, including psychological, return to work, and quality of life. Further studies with longitudinal follow-up are needed to further elucidate their associated risk factors in different stages post-injury, which could be useful for prevention of workers' long-term disability.